LITERASI KEUANGAN PEMILIK USAHA TERHADAP KEBERLANGSUNGAN USAHA (BUSINESS SUSTAINABILITY) PADA UMKM ROTAN DESA TRANGSAN, JAWA TENGAH - Ari Susanti; Elia Ardyan (BBM (Buletin Bisnis & Manajemen), 2019)
This study aims to analyze the factors that influence Financial Literacy of Business Owners, namelyfinancial literacy, financial planning, Level of Education Against Business Sustainability at RattanUMKM Trangsan Village, Gatak District, Central Java. Data collection techniques researchers doby observing and distributing questionnaires directly by visiting the object of research that is RattanUMKM Owner. Samples in this study amounted to 100 Rattan UMKM Business Actors. Dataprocessing uses SPSS 21. The results of this study indicate that the level of education has nosignificant effect on business continuity while financial literacy variables, financial planning havesignificant influence on business continuity.